Pelatihan Syukur Untuk Meningkatkan Self Compassion Pada Caregiver Anak Dengan Down Syndrome - Ismi Zulaehah; Sri Kushartati (JIP (Jurnal Intervensi Psikologi), 2017)
This study aims to explain the effect of grateful training in order to increase self compassion among  caregivers of children with down syndrome. Caregivers who get gratitude training were expected to have higher score at self compassion scale than the caregivers who did not get the treatment. The subjects of this study were seven adult caregivers of children with down syndrome, Muslim, female. They could be parents or closest relatives of children with down syndrome. The children with down syndrome were students of SLB PGRI Trimulyo. The kind of this research was pre-experimental with single pre-post test design. The collecting data used self compassion scale and it was analyzed by using Wilcoxon test. The hypothesis of this study was that gratitude training can increase self compassion among caregivers of children with down syndrome. The result of the study shows that there is significantly difference self compassion between before and after treatment was given. This proves that gratitude training can increase self compassion of caregivers of children with down syndrome.Keywords: caregivers, down syndrome, gratitude training, self compassion.